A High‐Performance and Long‐Term Air‐Stable CH3NH3PbI3/C8BTBT Heterojunction Photodetector Fabricated via Chemical Vapor Deposition. Issue 2 (4th January 2021) - Li, Xing; Xie, Pengshan; Mo, Xindi; Xiang, Yang; Xiao, Zhixing; Xiongsong, Tengxiao; Huang, Han; Sun, Jia; Dai, Guozhang; Yang, Junliang
Abstract : Organic–inorganic hybrid perovskites are considered as a class of star materials for optoelectronic devices. However, the stability is one of the big issues. Herein, an MAPbI3 perovskite film with high stability is fabricated using chemical vapor deposition (CVD). The stability and performance of the MAPbI3 photodetector are further improved by constructing an MAPbI3 heterojunction with the organic semiconductor C8BTBT. The MAPbI3 /C8BTBT heterojunction photodetector shows a wide spectral response range from ultraviolet to visible light and a fast response time of 30 ms/12 ms. Under laser irradiation at 405 nm, the responsivity of the MAPbI3 /C8BTBT heterojunction photodetector reaches 6.09 A W −1, which is an 11.9‐fold improvement as compared with the MAPbI3 photodetector (0.51 A W −1 ). After storage under ambient conditions (humidity of ≈35%) for 2 months, the MAPbI3 /C8BTBT heterojunction photodetector still exhibits excellent stability and the photocurrent maintains 93.7% of its initially measured value. The excellent stability under ambient conditions is likely the result of the stable MAPbI3 film that is fabricated via CVD and the protection of the organic semiconductor layer C8BTBT. The results provide a feasible route toward high‐performance and stable perovskite optoelectronic devices by combining CVD with perovskite heterojunctions. Abstract : An MAPbI3 perovskite film with high stability is fabricated using chemical vapor deposition (CVD). The stability and performance are further improved by constructing an MAPbI3 heterojunction with the organic semiconductor C8BTBT. After storage under ambient conditions with a humidity of ≈35% for 2 months, the MAPbI3 /C8BTBT heterojunction photodetector exhibits excellent stability, and the photocurrent maintains 93.7% of its initial value.